Factors affecting audit quality in registered companies in Libya - Belfagira, Khalid Gadhwar Emhemed (2015)
The study is motivated by academic available literature on the need to examine factors affecting audit quality in developing economy like Libya. The purpose of this study is to examine the factors affecting audit quality in registered companies in Libya. This study is based on three variables that are used to understand and analyze the level of audit quality within audit firm in Libya. The three variables that are measured in this current study are: independence auditor, audit firm size and audit fees. The data were collected through the distribution of questionnaires to 80 respondents in Libya and processed using Statistical Package for Social Science (SPSS) software for the purpose of this study. By using correlation and regression analysis, the findings of the study show that there is a positively significant relationship between independent auditor and audit firm size and audit quality. On the other hand, audit fees indicates a positive but insignificant correlation with audit quality